"I don't have any emotions": An ethnography of emotional labour and feeling rules in the emergency department. (11th February 2021) - Kirk, Kate; Cohen, Laurie; Edgley, Alison; Timmons, Stephen
Abstract: Aims: This study aims to apply Hochschild's theory of emotional labour to emergency care, and uncover the 'specialty‐specific' feeling rules driving this labour. Despite the importance of positive nurse well‐being, the emotional labour of nursing (a great influencer in wellbeing) remains neglected. Design and Methods: Ethnography enabled immersion in the ED setting, gathering the lived experiences and narratives of the ED nursing team. We undertook first‐hand observations at one major trauma centre ED and one district general ED including semi‐structured interviews (18). A reflexive and interpretive approach towards thematic analysis was used. Results: We unearthed and conceptualized four feeling rules born from this context and offer extensive insights into the emotional labour of emergency nurses. Conclusion: Understanding the emotional labour and feeling rules of various nursing specialties offers critical insight into the challenges facing staff ‐ fundamental for nursing well‐being and associated retention programs. Impact: What problem did the study address? What were the main findings? Where and on whom will the research have impact? Academically, this research expands our understanding ‐ we know little of nurses' feeling rules and how specialties influence them. Clinically, (including service managers and policy makers) there are practical implications for nurse well‐being. 摘要: 目的: 本研究旨在将霍赫希尔德的情绪劳动理论应用于急诊护理中, 并对推动此类劳动的"特殊"情绪规则进行披露。护士幸福感极为重要, 但目前, 护士的情感劳动 (对幸福感有巨大影响) 仍然遭到忽视。 设计和方法: 人种学常见于ED, 因此, 应收集ED护理团队的生活经验和叙述性资料。目前, 我们已在主要创伤中心ED和普通ED进行观察, 并开展半结构化访谈(18)。主题分析过程中, 采用了自反和解释性方法。 结果: 我们发掘四个由此产生的情感规则, 将其概念化, 并为急诊护士的情绪劳动提供广泛见解。 结论: 了解各类护理人员的情感劳动和情感规则, 有助于深入了解职员面临的挑战, 而此也是护理健康和相关保留项目的基础。 影响: 该研究解决了什么问题? 主要调查结果是什么? 本研究将在何处产生影响, 主要针对谁? 就学术层面而言, 本研究将扩大人们对护士情感规则和专业影响的理解——目前, 人们对此知之甚少。临床层面而言, (包括服务经理和政策制定者) 本研究对护士健康有实际意义。